A study on job satisfaction of agents in AXA Affin Life Insurance Berhad / Mohd Afiq Md Jaafar - Md Jaafar, Mohd Afiq (Faculty of Business and Management, 2010)
In chapter 1, in simple word it was the introduction stage of the research, which include the role of life insurance agents, the company’s background, the problem statement stating the problem of agents job satisfaction in AXA AFFIN Life Insurance Berhad, the research objective and research question which the researcher has to answer through his finding and the theoretical framework which the researcher has to construct to find the answer to the research question and research objective. The independent variable, which the researcher find from the past research are organizational culture, reward and job scope influenced the job satisfaction of life insurance agents.